Deciphering the termination of the Messinian salinity crisis: the alkenone record of the Miocene-Pliocene transition in the northern Mediterranean - Francesco Pilade; Iuliana Vasiliev; Daniel Birgel; Francesco Dela Pierre; Marcello Natalicchio; Alan Maria Mancini; Giorgio Carnevale; Rocco Gennari (PANGAEA, 2024)
The late Miocene Messinian salinity crisis (MSC; 5.97–5.33 Ma) transformed the Mediterranean basin into the youngest salt giant in Earth history. The paleoenvironment and the paleo-water depth of the Mediterranean basin during the terminal phase of the MSC, i.e., the Lago-Mare event, are still uncertain because of the paucity and uncertainty about the micropaleontological record. This study uses the distribution of C:37, C:38 and C:39 long-chain alkenones produced by haptophyte algae in combination with micropaleontological data and δ18O-based paleo-salinity indicators to reconstruct the paleoenvironmental conditions in the Northern Mediterranean basin across the Miocene-Pliocene boundary, dated at 5.33 Ma. The results suggest that the Mediterranean basin was already receiving influxes from the Atlantic Ocean before the end of the MSC, resulting in a progressive return to marine conditions proceeding from south to north, i.e., from the more distal to proximal areas. Finally, fully marine conditions was established at the base of the Pliocene (5.33 Ma). The study highlights the reliability of alkenone-based paleo proxies for environmental reconstructions, especially when body fossil records of primary producers are scarce or problematic.